2011
DOI: 10.5090/kjtcs.2011.44.6.413
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Sleeve Lobectomy versus Pneumonectomy for Lung Cancer

Abstract: BackgroundSleeve lobectomy for lung cancer in close proximity to or involving the carina is widely accepted. Operative morbidity and mortality rates, recurrence, and survival rates have varied considerably across studies.Materials and MethodsFrom March of 2005 to July of 2010, sleeve lobectomy was performed in 19 patients and pneumonectomy was performed in 20 patients. In this paper, the results of sleeve lobectomy and pneumonectomy for patients with lung cancer will be compared and evaluated.ResultsThere were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 18 publications
0
0
0
Order By: Relevance
“…[ 24 ] Similarly, in a propensity score analysis by Chen et al,[ 25 ] the superiority of sleeve lobectomy was emphasized in terms of shortand long-term survival. Lee et al[ 26 ] reported that pneumonectomy was superior to BSL in terms of three-year overall survival and disease-free survival, although the difference was not statistically significant.…”
Section: Resultsmentioning
confidence: 99%
“…[ 24 ] Similarly, in a propensity score analysis by Chen et al,[ 25 ] the superiority of sleeve lobectomy was emphasized in terms of shortand long-term survival. Lee et al[ 26 ] reported that pneumonectomy was superior to BSL in terms of three-year overall survival and disease-free survival, although the difference was not statistically significant.…”
Section: Resultsmentioning
confidence: 99%